Comparative Efficacy of Topical Pertmehrin, Crotamiton and Sulfur Oint-ment in Treatment of Scabies - Celestyna Mila-Kierzenkowska; Alina Woźniak; Ewa Krzyżyńska-Malinowska; Lucyna Kałużna; Roland Wesołowski; Wojciech Poćwiardowski; Marcin Owcarz (Tehran University of Medical Sciences, 2017)
Background:  Scabies is an ectoparasitic infection, which occurs because of direct skin-to skin contact. The ideal treatment modality is still unclear and further research on this topic is warranted. The aim of the study was to compare the efficacy and safety of the topical scabicides: permethrin, crotamiton and sulfur ointment. Methods: Fifty four patients with diagnosed scabies were randomly divided into three treatment groups. The first group received 5% permethrin cream twice with one week interval, the patients from the second group were given crotamiton lotion for two days twice with one week interval, while the third group received 10% sulfur ointment for two or three weeks. All patients were followed up at 1, 2 and 4 weeks intervals. Results: At one-week follow up the cure rate was significantly higher at permethrin-treated group when compared to crotamiton group (P< 0.001) and sulfur group (P< 0.001). At the end of two-week interval, the cure rate at permethrin group was 100%, while at crotamiton group, 66.7% and in sulfur group 38.9% (P< 0.001). At 4-week follow up the applied treatment was effective in all studied individuals. Conclusion: The topical application of permethrin, crotamiton and sulfur was equally efficacious at 4-week follow up, however permethrin cream showed faster improvement at first and second follow up. Acquiring permethrin is considered as expensive option and crotamiton lotion seems to be cost-less alternative to this cream.